INTERNATIONAL TREATY ON PLANT GENETIC RESOURCES FOR FOOD AND AGRICULTURE AS A BASIS FOR LIMITING INTELLECTUAL PROPERTY OF PLANT BREEDERS IN SERBIA - Veselinović, Janko P.; Milošević, Mirjana; Počuča, Sara (Economics of Agriculture, 2014)
It is widely accepted that new plant varieties are protected as a form of intellectual property. Serbian legislation and international conventions protect new plant varieties, either through sui generis protection or by patent rights. However, International Treaty on Plant Genetic Resources for Food and Agriculture, also signed by Serbia, has endangered the rights of plant breeders in Serbia, because the greatest number of plant varieties in Serbia is not protected as intellectual property. On the other hand, the Treaty offers the possibility to natural and legal persons from other signatory countries to use new plant varieties of Serbian plant breeders. Seeing as the varieties are not protected, there is a possibility for the plant breeders rights to be endangered. The goal of this paper is to try and consider the legal consequences, answering certain open questions regarding the protection of intellectual property in this fled. A method of parallel comparison was used.